Дослідниця античної історії та культури (до 100-річчя від дня народження Ф.М. Штітельман) - Буйських, С.Б.; Чуєва, К.Є. (Археологія, 2014)
Висвітлено наукову біографію відомого українського вченого-антикознавця Ф.М. Штітельман. В январе 2014 г. исполнилось 100 лет со дня рождения Фани Моисеевны Штительман (1914—1992) — известно го украинского ученого, признанного специалиста в области античной археологии, искусствоведа, плодотворно разрабатывавшего в своих трудах актуальные вопросы античного искусства — как Северного Причерноморья, так и Древней Греции и Рима в целом.
Данная статья является первой в историографии попыткой составить очерк научной биографии Ф.М. Шти тельман и дать объективную оценку ее научного наследия. В статье приведены основные биографические сведе ния и рассмотрены два периода научной деятельности Ф.М. Штительман: археологические исследования Ольвии и ее сельскохозяйственной округи в рамках экспедиций Института археологии УССР (1944—1954 гг.), а также изучение и пополнение фонда античного искусства Киевского музея западного и восточного искусства (ныне Национальный музей искусств им. Богдана и Варвары Ханенко) на протяжении 1955—1971 гг. in January 2014, 100 year passed since Fania Moiseyivna shtitelman was born (1914—1992). she was a famous ukrainian scholar, a wellknown specialist in Classical archaeology and art who fruitfully developed in her works topical issues of an cient Greek art, both of north coast of the Black sea, and of ancient Greece and rome as a whole.
The article is the first attempt made in historiography to create an outline of F.M. shtitelman’s scientific biography and to present an objective evaluation of her scientific heritage. it presents the main biographic evidences and discusses two periods in F.M. shtitelman’s scientific activity: archaeological research in Olbia and its rural vicinity within the expedition of the institute of archaeology of the ussr (1944—1954), and also the study and completion of the ancient Greek art col lection in the Kyiv Museum of the Western and eastern art (today the Bohdan and varvara Khanenko national Museum of arts) during the period between 1955 and 1971.